2022
DOI: 10.1186/s10194-022-01479-9
|View full text |Cite
|
Sign up to set email alerts
|

Persistent headache after first-ever ischemic stroke: clinical characteristics and factors associated with its development

Abstract: Background It is poorly described how often headache attributed to stroke continues for more than 3 months, i.e. fulfils the criteria for persistent headache attributed to ischemic stroke. Our aims were: 1) to determine the incidence of persistent headache attributed to past first-ever ischemic stroke (International headache society categories 6.1.1.2); 2) to describe their characteristics and acute treatment; 3) to analyse the prevalence of medication overuse headache in patients with persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
27
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 12 publications
6
27
1
Order By: Relevance
“…The HPCCAD is less documented in the literature, and few authors have studied its frequency (8,9); nevertheless, our work is in concordance with the findings of other studies in this field (8,9,(13)(14)(15). Schytz et al (8) showed that six months after dissection, five of 19 patients (26.3%) reported persistent headache attributable to the event.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The HPCCAD is less documented in the literature, and few authors have studied its frequency (8,9); nevertheless, our work is in concordance with the findings of other studies in this field (8,9,(13)(14)(15). Schytz et al (8) showed that six months after dissection, five of 19 patients (26.3%) reported persistent headache attributable to the event.…”
Section: Discussionsupporting
confidence: 91%
“…Tentschert et al (17) showed that 23% of patients with a persistent headache for three years after a stroke had previous history of headache, and our study showed a percentage almost three times higher (63.6%). On the contrary, Lebedeva et al (15) did not find a high prevalence of previous headache among patients with persistent headache after stroke, once more possibly explained by fine distinction between current and previous headaches.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations